Correlation between hypermobility score and injury rate in artistic gymnastics - Bukva, B.; Vrgoc, G.; Madic, D. M.; Sporiš, G.; Trajkovic, N. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Generalized joint hypermobility (GJH) is suggested as a contributing factor for injuries in young athletes and adults. It is presumed that GJH causes decreased joint stability, thereby increasing the risk of joint and soft tissue injuries during sports activities. The aim of this study was to determine the correlation between the hypermobility score (using the Beighton`s modification of the Carter-Wilkinson criteria of hypermobility) in gymnasts and injury rate, during the period of one year. METHODS: This study observed 24 artistic gymnasts (11-26 years old), members of Qatar National Team in artistic gymnastics. We examined the Beighton joint hypermobility screen and a seasonal injury survey. The gymnasts characteristics (age, gender) and gymnastics characteristics (training per day and number of years in training artistic gymnastics) and their relations to injury rate were also included. RESULTS: The most common injury was the lower back pain injury, followed by knee, shoulder, hip and ankle injuries. We found strong correlation of number of years gymnastics training and injury rate (P<0.001). There is no significant correlation in the numbers of training hours during one week and hypermobility score to numbers of injuries (P>0.05). CONCLUSIONS: According to this study there is no correlation between GJH and injury rate in artistic gymnasts in Qatar. Total training period in gymnastics have greater contribution in injury rate.